Moral realism in nursing - Edwards, Steven D. (Nursing philosophy, 2014)
For more than 15 years Professor Per Nortvedt has been arguing the case for moral realism in nursing and the health-care context more generally. His arguments focus on the clinical contexts of nursing and medicine and are supplemented by a series of persuasive examples. Following a description of moral realism, and the kinds of considerations that support it, criticisms of it are developed that seem persuasive. It is argued that our moral responses are explained by our beliefs as opposed to moral realities. In particular, two key arguments presented by Nortvedt are challenged: the so-called argument from convergence and the argument from clinical sensitivity. Both of these key planks in the case for moral realism are rejected, and an alternative ‘social conditioning’ account briefly sketched, which, it is claimed, has the same explanatory power as Nortvedt's thesis but does not rest on an appeal to independently existing moral properties.